Crop diversification through collective action: A case study of the Small Farmers large Field (SFLF) collective action farming model in Nalanda, Bihar - Mohanty, Samarendu; Kakraliya, Manish; Janakiraman, Deepa; Baruah, Sampriti; Kajod Mal Choudhary; Gathala, Mahesh K.; Krupnik, Timothy J. (TAFSSA, 2023)
The Transforming Agrifood Systems in South Asia (TAFSSA) initiative implemented the Small Farmers Large Field ((SFLF) collective farming model in two villages of Nalanda, Bihar with 97 potato farmers in Rabi 2022-23. The farmers were providedinput linkages, training in good agricultural practices and output linkages, among other things, to enhance their returns. This brief discussesa case study of ten potato farmers selected from the 97 participating farmers,growingKufri Pukhrajvariety of potatoes,who were encouraged to aggregate production and harvest potatoes 40 days early and take up a short-duration crop, such as red amaranthus.The underlying concept of this initiative was to create an opportunity for farmers, allowing them to explore crop diversification as a means to enhance their earnings..The study reveals that early harvest of potatoes combined with the cultivation of red amaranthus(Amaranthus Cruentus) locally calledLal Kanka resulted in higher net returns for farmers compared to traditional full-maturity harvest, showcasing the potential of crop diversification through intensification to improve farmers' income. The SFLF model also demonstrated the benefits of collective farming in sharing agricultural practices and resources, contributing to enhanced returns for the participating farmers.